1-[4-(4-Chlorophenyl)piperazin-1-yl]-3-(6-oxo-3,4-diphenyl-1,6-dihydropyridazin-1-yl)propan-1-one - Aydn A.; Akkurt M.; Doğruer D.S.; Büyükgüngör, Orhan (International Union of Crystallography (IUCr), 2012)
In the title compound, C(29)H(27)ClN(4)O(2), the six-membered ring of the pyridazine group is nearly planar [maximum deviation = -0.062 (2) Å] and its mean plane makes dihedral angles of 43.05 (9), 44.71 (10) and 72.57 (9)°, respectively, with the two phenyl and benzene rings. The piperazine ring has a chair conformation and its mean plane is almost perpendicular to the attached benzene ring, with a dihedral angle of 83.20 (16)°. In the crystal, mol-ecules are linked via two pairs of C-H⋯O inter-actions, which result in the formation of chains propagating along [10-1]. Neighbouring chains are linked via C-H⋯π inter-actions.
Keywords: Crystallography; QD901-999; Organic Papers; 3. Good health